Satisfaction of Beekeepers' towards the Services of National Horticulture Mission - Mehra, Jaya; Dangi, K. L.; Boyal, Vanpal Kumar (Indian Journal of Extension Education, 2014)
National Horticulture Mission was launched in the country in May 2005 as a centrally sponsored scheme to promote  holistic growth of the horticulture sector through an area based regionally differentiated strategies. The present  investigation was undertaken to evaluate the project with special reference to beekeeping under NHM. The evaluation of  the programme is essential for making the future programme more effective. Keeping this in view, the present study was  undertaken in Kota district of Rajasthan to study the satisfaction level of the beekeepers towards beekeeping programme  under National Horticulture Mission. The study indicated that majority (98.00 %) of the beekeepers had high satisfaction  level towards services provided by NHM for beekeeping programme. Besides, 2.00 per cent were moderately satisfied  with services provided by NHM. The beekeepers were highly satisfied about storage of produce (MPS 78.94), however,  they were least satisfied with availability of bee colonies (MPS 67.40).
Keywords: National horticulture mission; beekeeping; satisfaction level